Electrochemical hybrid catalyst containing nickel-iron diatomic metals, and carbon dioxide conversion system using the same

A nickel-iron two-atomic metal catalyst, connected via nitrogen-doped carbon nanostructures, addresses the inefficiencies of existing carbon dioxide reduction processes by enhancing carbon monoxide production at low overpotentials, offering cost-effective and stable performance.

JP2025015419AActive Publication Date: 2025-01-30
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2024072651
Authority / Receiving Office
JP · JP
Patent Type
Applications
Priority Date
2023-07-19
Filing Date
2024-04-26
Publication Date
2025-01-30
Estimated Expiration
2044-04-26

AI Technical Summary

Technical Problem

Existing electrochemical carbon dioxide reduction processes face challenges with low reaction speeds, poor product selectivity, and high energy requirements, particularly in the use of precious metal catalysts, which are costly and difficult to synthesize stably.

Method used

A nickel-iron two-atomic metal catalyst is developed, where nickel and iron are indirectly connected via nitrogen-doped carbon nanostructures, forming a single-atom catalyst that enhances carbon dioxide conversion activity and selectivity for carbon monoxide production at low overpotentials.

Benefits of technology

The catalyst achieves high carbon monoxide selectivity and current density with low overvoltage, using inexpensive transition metals, and is more economically viable than precious metal catalysts, while maintaining high catalytic activity and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025015419000001_ABST
    Figure 2025015419000001_ABST
Patent Text Reader

Abstract

To provide: a transition metal based electrochemical electrode catalyst available for carbon dioxide reduction that improves price competitiveness with better activity than noble metal catalysts such as Ag / C; a production method thereof; an electrode for carbon dioxide reduction reaction containing the catalyst; and a carbon dioxide reduction system including the catalyst.SOLUTION: An electrode catalyst comprises: a support comprising a nitrogen-doped carbon nanostructure; and Ni and Fe in the form of single atoms each supported on the support, where the Ni is bonded to four surrounding nitrogen atoms while the Fe is bonded to five surrounding nitrogen atoms, and where the Ni and Fe at the respective sites are adjacent to each other and are indirectly linked to each other via nitrogen, thereby forming an active site. The electrode catalyst exhibits high carbon monoxide selectivity and current density under a low overpotential condition during reduction of carbon dioxide to carbon monoxide.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to an electrochemical hybrid catalyst including nickel (Ni)-iron (Fe) diatomic metals and a carbon dioxide conversion system using the same. More specifically, the present disclosure relates to an electrochemical hybrid catalyst that shows high carbon monoxide selectivity and current density under low overpotential conditions during a reduction reaction that converts carbon dioxide to carbon monoxide by forming catalytic sites or active sites in a form in which two monatomic metals, nickel and iron, each bonded (or coordinated) with nitrogen, are adjacent to each other and indirectly linked via nitrogen (N) in a nitrogen (N)-doped carbon nanostructure ((NC) nanostructure) composite, and a carbon dioxide conversion system using the same. [Background technology]

[0002] Since the Industrial Revolution, the amount of carbon dioxide (CO2) generated has been increasing exponentially with the massive consumption of fossil fuels and the increase in the global population. Carbon dioxide is emitted into the atmosphere through human industrial and economic activities, and increases the greenhouse effect by adding carbon dioxide to the existing carbon cycle, which increases the temperature on the earth's surface and in the lower atmosphere, inducing global warming and climate change and emerging as a fatal factor threatening ecosystems.

[0003] As a result, greenhouse gas reduction plans have been announced in various countries around the world, and the burden of reducing carbon dioxide emissions is increasing across the industrial sector. Existing research has focused mainly on carbon dioxide capture and storage, but recently, intensive research has been conducted on technologies to turn generated carbon dioxide into resources, i.e., technologies to convert carbon dioxide into useful substances such as high-value-added fuels or platform compounds, as a way to realistically contribute to the target of a 37% reduction in greenhouse gas emissions by 2030 compared to the business as usual (BAU) outlook, which was specified in the 2015 Paris Climate Change Agreement.

[0004] As carbon dioxide conversion technologies, methods such as electrochemical conversion, photochemical conversion, chemical conversion using a catalyst, biological conversion, etc. have been proposed. In particular, electrochemical conversion technology (i) can be operated under room temperature / pressure conditions, (ii) the system is simple and modularized, (iii) it can increase the carbon dioxide net reduction rate when using new renewable energy, and (iv) it can be used as a new renewable energy storage technology by converting it into high-addition chemicals. In particular, the carbon dioxide reduction reaction (CO2RR), which reacts thermodynamically stable carbon dioxide with water, can produce various organic compounds, minimizing the emission of pollutants and is environmentally friendly. Thus, the high-addition chemicals and fuels produced by the carbon dioxide reduction reaction are promising solutions to the commercial-scale carbon cycle, energy crisis, and environmental pollution.

[0005] Nevertheless, the electrochemical carbon dioxide reduction process that has been studied to date has limitations due to low reaction rate, distribution of various products (low selectivity), and the occurrence of competing reactions such as hydrogen evolution reaction (HER). To overcome these technical barriers, electrochemical catalysts with higher catalytic activity and efficiency for carbon dioxide reduction are required. Existing research has presented various electrochemical carbon dioxide conversion catalysts, including metal-free catalysts, metal-based catalysts, and metal-organic framework (MOF)-based catalysts that provide high activity and selectivity. In particular, it has been reported that the use of precious metal catalysts such as gold (Au) and silver (Ag) among metal-based catalysts leads to excellent results in terms of current density and faradaic efficiency (FE) for carbon monoxide (CO).

[0006] However, precious metal catalysts are disadvantageous in terms of commercial use because they use expensive precious metals, and recently, interest has been growing in catalysts in which metals are dispersed (or supported) at single-atom size, i.e., single atom catalysts (SACs). Single atom catalysts can maximize carbon dioxide conversion activity by reducing the size of metal active sites to the atomic level of nano-size or less, and can provide a method for replacing expensive precious metals with inexpensive transition metals. In particular, since they have an extremely simplified and ideal structure, they have the advantage of being suitable for related research by copying theoretical results obtained by computational science, etc. (J.Phys.Chem.C,2013,117,9187-9195; Angew.Chem.Int.Ed.,2015,54,10758-10762, etc.). However, metal catalysts with single-atom size have a tendency to aggregate and form particles, making it difficult to commercially synthesize stable single-atom catalysts, and the costly and complicated synthesis process is an obstacle to their application in various fields. In particular, the structural simplicity of single-atom active sites limits the increase in catalytic efficiency of the carbon dioxide reduction process, which involves multiple proton-electron transfer steps.

[0007] Therefore, carbon-based metal-nitrogen catalysts ((MN) catalysts) that provide transition metal active sites in the form of single atoms have been developed, and these catalysts exhibit low cost, adjustable structures, high activity, and stability, and furthermore, the favorable coordination environment can promote the formation of active sites and catalytic mechanisms.

[0008] Currently, nickel (Ni) single-atom catalysts are known to be effective alternatives to noble metal catalysts because they show high activity and selectivity to carbon monoxide in carbon dioxide conversion reactions, but they still require a large amount of energy (high overpotential) to achieve high faradaic efficiency.

[0009] Therefore, there is a need for techniques to tailor the electronic structure of single-atom catalysts to improve their carbon dioxide conversion performance. Summary of the Invention [Problem to be solved by the invention]

[0010] In one embodiment of the present disclosure, there is provided a transition metal single atom catalyst and an electrochemical electrode including the same, which can provide superior carbon dioxide conversion activity and improve price competitiveness as compared to existing commercialized precious metal catalysts (e.g., Ag / C).

[0011] In another embodiment of the present disclosure, a carbon dioxide conversion system is provided that employs a catalyst that has higher carbon dioxide conversion activity and high selectivity for carbon monoxide compared to conventional techniques, and that can effectively remove carbon dioxide from exhaust gases emitted from power plants, steelworks, and the like. [Means for solving the problem]

[0012] According to the first invention, (i) a support comprising nitrogen-doped carbon nanostructures ((NC) nanostructures); and (ii) nickel (Ni) and iron (Fe), each in monoatomic form supported on said support; Including, where nickel (Ni) is linked to each of the four surrounding nitrogen atoms, while iron (Fe) is linked to each of the five surrounding nitrogen atoms, forming Ni-N4 sites and Fe-N5 sites; and A catalyst for carbon dioxide conversion is provided in which Ni at the Ni-N4 site and Fe at the Fe-N5 site are adjacent to each other and indirectly connected via nitrogen.

[0013] According to the second invention, a) forming an iron (Fe)-containing polymer / carbon composite by attaching a nitrogen-containing monomer to carbon and polymerizing in-situ using an iron-based oxidizing agent; b) depositing a nickel precursor onto the iron (Fe)-containing polymer / carbon composite to form a NiFe-polymer / carbon composite; c) pyrolyzing the NiFe-polymer / carbon composite to deposit nickel (Ni) and iron (Fe) in monoatomic form on a support comprising nitrogen-doped carbon (NC) nanostructures; Including, Here, nickel (Ni) is linked to each of the four surrounding nitrogen atoms, while iron (Fe) is linked to each of the five surrounding nitrogen atoms to form Ni-N4 sites and Fe-N5 sites, and the Ni in the Ni-N4 sites and the Fe in the Fe-N5 sites are adjacent to each other and indirectly linked via nitrogen, thereby providing a method for producing a catalyst for carbon dioxide conversion.

[0014] According to the third invention, Electrode substrate; and a diatomic metal catalyst loaded on said electrode substrate; An electrode for a carbon dioxide reduction reaction comprising: The diatomic metal catalyst is (i) a support comprising nitrogen-doped carbon nanostructures ((NC) nanostructures); and (ii) nickel (Ni) and iron (Fe), each in monoatomic form supported on said support; an electrochemical catalyst comprising: In the diatomic metal catalyst, nickel (Ni) is linked to each of the four surrounding nitrogen atoms, while iron (Fe) is linked to each of the five surrounding nitrogen atoms, forming Ni-N4 sites and Fe-N5 sites; and An electrode is provided in which Ni at the Ni-N4 site and Fe at the Fe-N5 site are adjacent to each other via nitrogen and indirectly connected to each other.

[0015] According to an exemplary embodiment, the loading of the diatomic metal catalyst in the electrode is 0.2 to 5 mg / cm. 2 may be in the range.

[0016] According to the fourth invention, an anode and a cathode as electrochemical electrodes electrically connected to an external power source; and an aqueous electrolyte disposed between the anode and the cathode; A carbon dioxide reduction system comprising: When a voltage is applied from the external power supply, oxygen is generated from the anode side and carbon monoxide is generated from the cathode side, the cathode comprises a diatomic metal catalyst loaded on an electrode substrate; wherein the diatomic metal catalyst is (i) a support comprising nitrogen-doped carbon nanostructures ((NC) nanostructures); and (ii) nickel (Ni) and iron (Fe), each in monoatomic form supported on said support; an electrochemical catalyst comprising: In the diatomic metal catalyst, nickel (Ni) is linked to each of the four surrounding nitrogen atoms, while iron (Fe) is linked to each of the five surrounding nitrogen atoms, forming Ni-N4 sites and Fe-N5 sites; and A system is provided in which Ni at the Ni-N4 site and Fe at the Fe-N5 site are adjacent to each other and indirectly linked via nitrogen. Effect of the Invention

[0017] In the nickel (Ni)-iron (Fe) biatomic metal catalyst according to the embodiment of the present disclosure, two kinds of monatomic transition metals (i.e., nickel (Ni) and iron (Fe)) bonded (or coordinated) to nitrogen in the nitrogen-doped carbon nanostructure are supported in a form in which they are adjacent to each other and indirectly linked (or bonded) through the intermediation of nitrogen. As a result, the nickel (Ni)-iron (Fe) biatomic metal catalyst can achieve better carbon dioxide conversion performance (low overpotential, high current density, and high carbon monoxide selectivity) than a monometallic monatomic catalyst or a biatomic metal catalyst in which two kinds of nickel (Ni) and iron (Fe) are directly bonded in a monatomic form. In addition, it is advantageous from an economical perspective because it can provide improved electrochemical catalytic activity compared to commercial precious metal-based catalysts in the carbon dioxide reduction reaction while using inexpensive transition metals or base metals. The nickel (Ni)-iron (Fe) bimetallic catalyst according to this embodiment can be produced by a simple procedure such as an ion adsorption method, and can be applied to the electrode (i.e., the cathode) of an electrochemical system for carbon dioxide reduction reaction, whereby carbon dioxide can be reduced while at the same time producing highly-additive compounds (e.g., carbon monoxide, which is a component of synthesis gas). Therefore, it is expected to be widely applied in the future. [Brief description of the drawings]

[0018] [Figure 1] FIG. 1 illustrates a schematic diagram of a process for producing a nickel (Ni)-iron (Fe) diatomic metal catalyst (NiFe-DAC) according to an exemplary embodiment. [Figure 2A] 1 is a HAADF-STEM / element mapping photograph of a nickel (Ni)-iron (Fe) diatomic metal catalyst (NiFe-DAC) according to an embodiment. [Figure 2B] 1 is a HAADF-STEM / element mapping photograph of a nickel (Ni)-iron (Fe) diatomic metal catalyst (NiFe-DAC) according to an embodiment. [Figure 2C] 1 is a HAADF-STEM / element mapping photograph of a nickel (Ni)-iron (Fe) diatomic metal catalyst (NiFe-DAC) according to an embodiment. [Diagram 3] 1 shows X-ray diffraction (XRD) patterns of a nickel (Ni)-iron (Fe) diatomic metal catalyst (NiFe-DAC) according to an embodiment and an Fe single atom catalyst (Fe-SAC) according to a comparative example. [Figure 4] 1 is a graph showing the results of XPS (X-ray Photoelectron Spectroscopy) analysis of a nickel (Ni)-iron (Fe) diatomic metal catalyst (NiFe-DAC) according to an embodiment and an Fe single atom catalyst (Fe-SAC) according to a comparative example. [Figure 5A] 1 is a graph showing the results of an EXAFS (Extended X-ray absorption fine structure) analysis of a nickel (Ni)-iron (Fe) diatomic metal catalyst (NiFe-DAC) according to an embodiment and a Fe single atom catalyst (Fe-SAC) according to a comparative example. [Figure 5B] 1 is a graph showing the results of an EXAFS (Extended X-ray absorption fine structure) analysis of a nickel (Ni)-iron (Fe) diatomic metal catalyst (direct bond; NiFe-DAC(Direct)) according to a comparative example. [Figure 6] 1 is a graph showing the results of BET analysis of a catalyst (NiFe-DAC) according to an embodiment and a catalyst (Fe-SAC) according to a comparative example. [Figure 7] 1 is a graph showing the faradaic efficiency (FE) for carbon monoxide production for a nickel (Ni)-iron (Fe) diatomic metal catalyst (NiFe-DAC) according to an embodiment, and a single Fe atom catalyst (Fe-SAC) according to a comparative example, a commercial Ag / C catalyst, and a nickel (Ni)-iron (Fe) diatomic metal catalyst (direct bond; NiFe-DAC(Direct)). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The present invention can be achieved by the following description. The following description should be understood as describing a preferred embodiment of the present invention, and the present invention is not necessarily limited thereby. In addition, the attached drawings are for the purpose of aiding understanding, and the present invention is not limited thereto, and details regarding individual configurations can be properly understood by the specific meaning of the related description described below.

[0020] As used herein, the term "catalyst" refers to a component that increases the rate of an electrochemical reaction and participates in the reaction itself but is not consumed by the reaction itself. In a narrower sense, the term may refer to a component that promotes the reaction mechanism of donating or accepting electrons in the carbon dioxide reduction reaction to produce carbon monoxide and / or the oxygen production reaction.

[0021] "Electrochemical catalyst" means a catalyst that participates in an electrochemical reaction, typically functioning at an electrode surface or which may be the electrode surface itself.

[0022] The term "electrochemical carbon dioxide conversion reaction" refers generally to a reaction in which carbon dioxide is reduced to useful carbon compounds by inputting electrical energy to generate a potential difference between two electrodes (a cathode and an anode) and inducing the transfer of electrons, more specifically, to a reaction in which carbon dioxide is reduced to carbon monoxide.

[0023] "Nanostructure" refers to any nanoscale object having a feature or texture having a dimension or size on the nanoscale (e.g., about 0.1-1000 nm, preferably 1-100 nm), such as nanofillers, nanorods, nano-walls, nanowires, nanowebs, etc.

[0024] "Single atom form" is understood to mean a form in which the active metal attached or fixed to the support is present in isolated or individualized atomic form.

[0025] "Indirect" means that two atoms or ions are not directly linked to each other, but are linked through another atom or group, whereas "Direct" means that two atoms are directly linked to each other (e.g., metal-metal bonding).

[0026] The term "electrode" as used herein refers to a conductive structure that is electrically connected to an external power source in a carbon dioxide reduction reaction (CORR) system and is typically externally separated from the external power source, and refers to a cathode where a carbon dioxide reduction reaction occurs when a voltage is applied from the external power source, and an anode where an oxidation reaction occurs.

[0027] "Catalytic electrode" refers to a current collector loaded with a catalyst absorbed on or separately electrically connected to a current collector, where it is understood that the catalyst becomes associated with the current collector by changing its oxidation state and / or by dynamic equilibrium with the aqueous medium when exposed to an aqueous medium (e.g., an aqueous electrolyte solution, etc.).

[0028] "Electrochemical electrode" refers to an electrode structure in which a catalytic component that promotes the carbon dioxide reduction reaction is mixed into or attached to the substrate of the electrode (cathode and / or anode).

[0029] "Overpotential" means a voltage other than the thermodynamic reduction or oxidation voltage required to obtain a desired catalytic activity. As used herein, overpotential means the voltage that must be applied to an electrode to cause a carbon dioxide reduction reaction to occur minus the thermodynamic voltage required for that reaction.

[0030] "Pyrolysis" refers to a chemical process in which certain substances are converted into other substances by heat, with or without the presence of gases, typically the pyrolysis of organic substances to form gas and / or liquid products, which may produce a solid residue with increased carbon content. Pyrolysis occurs in an inert gas (e.g., nitrogen, argon, etc.) or reactive gas (e.g., ammonia, hydrogen, etc.) atmosphere.

[0031] Terms such as "left side" or "right side" may be understood to describe the relative positional relationship between components or members, and the terms "located on the left side" or "located on the right side" are understood to express the relative positional relationship both in a state of contact with a specific object as well as in a state of no contact.

[0032] In this specification, when a numerical range is specified as a lower limit and / or an upper limit, it is understood that any other combination of numerical ranges within the numerical range is also disclosed. For example, when it is described as "1 to 5", it may include not only 1, 2, 3, 4, and 5, but also any other combination of numerical ranges therebetween.

[0033] In this specification, when any component or member is described as being "connected" to another component or member, unless otherwise specified, it is understood that this includes not only when it is directly connected to the other component or member, but also when it is connected via another component or member.

[0034] Similarly, the term "contact" is understood to include not only direct contact, but also contact via another component or member.

[0035] When a certain component is described as "comprising," this means that other components may also be included, unless otherwise specified.

[0036] Single-atom catalysts for carbon dioxide conversion The electrochemical catalyst according to an embodiment of the present disclosure may be used as a cathode catalyst in a carbon dioxide reduction system in which an anode or oxidizing electrode and a cathode or reducing electrode are electrically connected to an external power source and an electrolyte (specifically, an aqueous electrolyte) is filled between the anode and the cathode. Such an electrochemical carbon dioxide conversion reaction is a process in which carbon dioxide is electrolyzed together with an aqueous medium to obtain a desired product, and a carbon dioxide reduction reaction occurs at the cathode (reducing electrode) as shown in the following reaction formula 1 by electrical energy supplied from an external power source, and an oxygen generation reaction occurs by oxidation at the anode (oxidizing electrode) as shown in the following reaction formula 2.

[0037] [Reaction Scheme 1] CO2+H2O+2e - → CO+2OH -

[0038] [Reaction Scheme 2] 2OH - → 1 / 2O2+H2O+2e -

[0039] In particular, the detailed mechanism of the carbon dioxide reduction reaction at the cathode can be expressed as shown in Reaction Scheme 3 below.

[0040] [ka]

[0041] According to this embodiment, a catalyst is provided in which two metals, i.e., nickel (Ni) and iron (Fe), are supported on a nitrogen-doped carbon nanostructure in a monatomic form as an electrochemical catalyst for promoting the carbon dioxide reduction reaction (CO2RR) occurring at the cathode. In this case, the catalyst is a hybrid catalyst in which nickel and iron are simultaneously present in a monatomic form, and are adjacent to each other in an atomic state (monatomic). As a result, in the carbon dioxide conversion mechanism according to Reaction Scheme 3, both the adsorption and activation of carbon dioxide and efficient carbon monoxide desorption are effectively performed.

[0042] It should also be noted that because nickel and iron are not directly linked to each other but interact in a state of being indirectly linked via nitrogen, such a catalyst can achieve high carbon dioxide conversion and selectivity to carbon monoxide even under low overpotential conditions compared to single metal single atom catalysts (e.g., Fe-single atom catalysts and Ni-single atom catalysts) and diatomic catalysts (DAC) in which nickel (Ni) and iron (Fe) are directly linked to each other.

[0043] In one embodiment, the biatomic metallic catalyst comprises nickel (Ni) and iron (Fe), each in monoatomic form, dispersed or supported on a support comprising nitrogen-doped carbon nanostructures.

[0044] According to an exemplary embodiment, the bimetallic catalyst may exhibit porosity. Illustratively, the bimetallic catalyst may exhibit micropore (preferably, 2 nm or less) porosity. In this case, the specific surface area (BET) of the catalyst may be, for example, about 100 to 300 m. 2 / g, preferably about 120 to 250 m 2 / g, more preferably about 130 to 180 m 2 / g. The pore volume is about 0.1 to 0.5 cm 3 / g, preferably about 0.15 to 0.4 cm 3 / g, more preferably about 0.2 to 0.3 cm 3 / g. The numerical ranges given above are understood to be for illustrative purposes only.

[0045] According to an exemplary embodiment, the nitrogen content in the nitrogen-doped carbon nanostructure usable as a support may be, for example, in the range of about 1 to 12 atomic %, preferably about 2 to 10 atomic %, more preferably about 4 to 8 atomic %. In this regard, the amount of nitrogen doping is a factor that affects the degree of bonding with metal atoms, and is preferably appropriately adjusted within the aforementioned range. However, the present disclosure is not limited thereto.

[0046] According to this embodiment, in the carbon dioxide conversion catalyst, two transition metals, i.e., nickel (Ni) and iron (Fe), are supported in a single-atom form or an atomic-scale isolated form so as to form active sites during the carbon dioxide conversion reaction and to form an electronic structure of the active sites suitable for the carbon dioxide conversion reaction through interaction.

[0047] Although the present disclosure is not bound by a particular theory, the reason for adopting a combination or pair of nickel and iron as diatomic metals (transition metals) in a catalyst for carbon dioxide conversion may be explained as follows: nickel has properties that are favorable for carbon monoxide desorption, and iron is favorable for the activation step (formation of a COOH reaction intermediate), which is the initial step of carbon dioxide conversion. In this way, by configuring the active metals in the catalyst as a combination or pair of nickel and iron, it is possible to change the electronic structure by using effective electron transfer between nickel and iron. As a result, by adjusting the activation energy of the carbon dioxide conversion step, it is possible to ultimately maximize the catalytic performance, which is considered to be an advantage over other combinations of diatomic transition metals.

[0048] According to exemplary embodiments, the biatomic metallic catalysts according to the present invention may optionally further comprise other metals or transition metals in addition to the combination of nickel and iron for further modification or modification, in which case the additional metals may also be introduced in monoatomic form.

[0049] According to this embodiment, nickel and iron may each be supported in a form bonded (specifically, coordinated) with nitrogen atoms in the nitrogen-doped carbon nanostructure. Specifically, nickel (Ni) is linked to each of the four surrounding nitrogen atoms to form Ni-N4 sites, and iron (Fe) is linked to each of the five surrounding nitrogen atoms to form Fe-N5 sites. Such Ni-N4 sites and Fe-N5 sites can act as active sites for the carbon dioxide reduction reaction.

[0050] It should be noted that, according to one embodiment, nickel and iron in the catalyst are adjacent to each other but indirectly connected via nitrogen, unlike the conventionally known Ni-Fe diatomic catalysts in which Ni and Fe are directly connected. In this case, the nitrogen interposed between nickel and iron may be a single nitrogen and / or multiple nitrogens (e.g., NN).

[0051] On the other hand, according to an exemplary embodiment, the respective contents of nickel (Ni) and iron (Fe) in the catalyst may be, for example, about 0.1 to 10 wt % (preferably about 0.2 to 8 wt %, more preferably about 0.4 to 5 wt %, and particularly preferably about 0.7 to 1.5 wt %) and about 0.1 to 10 wt % (preferably about 0.2 to 8 wt %, more preferably about 0.4 to 5 wt %, and particularly preferably about 0.6 to 1.3 wt %).

[0052] The relative loading amounts of nickel (Ni) and iron (Fe) in the catalyst may be determined in consideration of the degree of interaction between them. For example, the atomic ratio of nickel (Ni) and iron (Fe) can be adjusted within a range of, for example, 1: about 0.4 to 1.6, preferably 1: about 0.6 to 1.4, and more preferably 1: about 0.8 to 1.2.

[0053] Method for producing a catalyst for carbon dioxide conversion According to another embodiment of the present disclosure, there is provided a method for preparing the aforementioned nickel (Ni)-iron (Fe) bimetallic catalyst for carbon dioxide conversion. In this regard, FIG. 1 is a schematic diagram illustrating a procedure for preparing the bimetallic catalyst according to an exemplary embodiment, specifically, an ion adsorption method.

[0054] Referring to the figure, first, carbon (or carbon particles) is provided.

[0055] In the illustrated embodiment, the carbon has good conductivity and is preferably selected from types that have properties that allow easy introduction of functional groups. According to an exemplary embodiment, the carbon may be at least one selected from carbon black, graphene, carbon nanotubes (CNTs), fullerenes, etc. However, in consideration of economics, it is preferable to use carbon black. The above types are understood to be exemplary and are not necessarily limited thereto.

[0056] In this regard, carbon may be produced by a method known in the art, or a commercially available type may be purchased and used. As an example, an organic compound as a carbon source may be converted into carbon by a carbonization process (specifically, pyrolysis). Examples of such organic compounds include polymers (e.g., thermoplastic resins, etc.), low molecular weight organic compounds, etc., which may be used alone or in combination of two or more, and biomass may also be used. Exemplary types of carbon sources may be at least one selected from conductive polymers, various petroleums, coal, graphite, acetylene gas, etc. The above-mentioned carbonization process is known in the art, and further detailed description will be omitted.

[0057] Meanwhile, according to an exemplary embodiment, the shape of the carbon (or carbon particles) may be, for example, spherical, elliptical, rod-like, plate-like, etc., and more specifically, may be in the form of a spherical powder. In addition, in the illustrated embodiment, since the carbon may have a nanoscale dimension, the average particle size thereof may be, for example, in the range of about 10 to 200 nm, preferably about 20 to 150 nm, and more preferably about 30 to 80 nm. In this case, the average particle size of the particles can be measured by a scanning electron microscope (SEM) or a transmission electron microscope (TEM).

[0058] According to an exemplary embodiment, carbon may advantageously have good electrical conductivity to conduct an effective electrochemical reaction, for example, a conductivity of at least about 1.5 Scm. -1 , preferably at least about 2 Scm -1 , more preferably at least about 2.5 Scm -1 , and particularly preferably at least about 2.7 Scm -1 may be also possible.

[0059] Meanwhile, referring to FIG. 1 again, when carbon (or carbon particles) is provided, a step of forming an iron (Fe)-containing polymer / carbon composite may be performed by polymerizing a nitrogen-containing monomer in-situ on the carbon through a chemical oxidation method using an iron-based compound as an oxidant. However, according to an exemplary embodiment, prior to the polymerization reaction, impurities (e.g., inorganic impurities), metals (e.g., alkali metals, alkali metal oxides, alkaline earth metals and / or alkaline earth metal oxides) that can be contained in the carbon may block the pore structure in the carbon, and in order to remove them, acid washing or acid leaching may be optionally performed. At this time, the acid that can be used may be at least one selected from, for example, sulfuric acid, nitric acid, phosphoric acid, hydrochloric acid, formic acid, and the like, and more specifically, sulfuric acid and / or hydrochloric acid may be used. In addition, the acid may be used in the form of an aqueous acid solution during acid washing, and the concentration may be adjusted to, for example, about 1 to 8 M, preferably about 3 to 7 M, but this is understood as an exemplary purpose.

[0060] According to the illustrated embodiment, iron (Fe) can be introduced by adding a monomeric nitrogen source (nitrogen-containing monomer) to carbon (specifically, a carbon dispersion liquid) and polymerizing it in-situ in the presence of an iron-based oxidant, thereby contacting and adhering (or coating) the carbon with the polymeric nitrogen source (forming an iron (Fe)-containing polymer / carbon composite).

[0061] In this regard, carbon may be dispersed in a liquid medium (dispersion medium) first, and then a nitrogen source (i.e., a nitrogen-containing monomer) may be added. In this case, the liquid medium may be at least one selected from water, an aliphatic alcohol having 1 to 4 carbon atoms (e.g., methanol, ethanol, propanol (e.g., n-propanol and / or iso-propanol), and / or n-butanol), and specifically, propanol may be used. According to a specific embodiment, a mixed solvent (or mixed solution) of alcohol and water may be used as the liquid medium. In this case, the volume ratio of alcohol:water may be adjusted, for example, in the range of about 1.5 to 5:1, preferably about 2 to 4:1, and more preferably about 2.5 to 3.5:1, but this is understood as an exemplary purpose.

[0062] According to an exemplary embodiment, the nitrogen-containing monomer added to the carbon dispersion liquid is not limited to a specific compound, and one or more precursors can be used as long as it contains both nitrogen and carbon in the compound and can be carbonized by a heat treatment process such as pyrolysis after polymerization. In a specific embodiment, examples of the nitrogen-containing monomer include urea, melamine, ammonia, adenine, pyrrole, acrylonitrile, phenanthroline, pyrazole, vinylpyridine, pyrimidine, piperazine, pyran, carbamide, morpholine, imidazole, 1-methylimidazole, 2-methylimidazole, quinoxaline, aniline, benzimidazole, ethylenediamine, and cyanamide. According to a specific embodiment, pyrrole can be used as the nitrogen-containing monomer, and since pyrrole monomer contains one nitrogen per molecule, it is advantageous in that carbon can be effectively doped with nitrogen by a polymerization reaction, and the carbon surface can also be uniformly doped with nitrogen.

[0063] In this regard, the amount of the nitrogen-containing monomer added to the carbon dispersion may be determined according to the amount of nitrogen to be finally mixed (doped) into the carbon (i.e., the nitrogen doping amount), but since not all of the added nitrogen source is doped, it may be added in an amount in excess of the actual mixed amount. For example, the amount of the nitrogen-containing monomer relative to the carbon may be about 0.01 to 1, preferably about 0.05 to 0.8, and more preferably about 0.1 to 0.4, by weight.

[0064] For example, the nitrogen-containing monomer may be added in a form dispersed in water, and in this case, the concentration of the nitrogen-containing monomer in the dispersion may be adjusted, for example, in the range of about 0.5 to 5 mmol, preferably about 1 to 4 mmol, and more preferably about 1.5 to 3 mmol, which is understood as an illustrative example.

[0065] Meanwhile, according to an exemplary embodiment, the iron-based oxidizing agent may be selected from a type that satisfies the requirement of having high solubility in water or alcohol, and typically, an Fe(II) oxidizing agent and / or an Fe(III) oxidizing agent may be used. For example, the Fe(II) oxidizing agent (compound) may be at least one selected from the group consisting of Fe(NO3)2, FeSO4, Fe(acac)2, Fe(tfac)2, Fe(OAc)2, FeCl2, FeBr2, and FeI2, and hydrates thereof. The Fe(III) oxidizing agent (compound) may be at least one selected from the group consisting of Fe(NO3)3, Fe2(SO4)3, Fe(acac)3, Fe(tfac)3, Fe(OAc)3, Fe(OTs)3, Fe(OTf)3, FeCl3, FeBr3, and FeI3, and hydrates thereof. According to a specific embodiment, FeCl3·6H2O may be used as the iron-based oxidizing agent.

[0066] The amount of the iron-based oxidant used may be, for example, about 0.2 to 5 times, preferably about 0.6 to 4 times, and more preferably about 1 to 3 times, based on the moles of the monomer. In addition, the iron-based oxidant may be prepared in the form of a solution (specifically, an aqueous solution) for an effective polymerization reaction, and then added to the carbon dispersion liquid into which the nitrogen-containing monomer has been introduced. In this case, the concentration of the iron-based oxidant solution may be adjusted, for example, in the range of about 1 to 10 mmol, preferably about 2 to 7 mmol, and more preferably about 3 to 5 mmol, but this is understood as an illustrative example.

[0067] According to an exemplary embodiment, the polymerization reaction temperature is not particularly limited, and may be adjusted typically in the range of about 5 to 60° C., preferably about 10 to 50° C., and more preferably about 20 to 40° C. The polymerization time may be, for example, about 0.1 to 30 hours, preferably about 1 to 20 hours, and more preferably about 1.5 to 10 hours.

[0068] In this way, when the iron (Fe)-containing polymer / carbon composite is formed, a nickel precursor can be attached or introduced thereto to form a NiFe-polymer / carbon composite. In this regard, the nickel precursor may be introduced into the composite by a supporting method known in the art, for example, an impregnation method (specifically, an incipient wet impregnation method), a precipitation method, a strong reducing agent reduction method, a polyol process, etc. can be applied. The basic principles of the above-mentioned supporting methods are known in the art, and therefore the description thereof will be omitted.

[0069] In an exemplary embodiment, the nickel precursor may be introduced into the iron (Fe)-containing polymer / carbon composite by ion adsorption, and is typically used in the form of a water-soluble compound, and may be, for example, a halide, an organic acid salt, an inorganic acid salt, a hydroxide, a complex, a combination thereof, or a hydrate form of the above-mentioned compound. As an example, the inorganic acid salt may be at least one selected from nitrates, sulfates, carbonates, halides, etc., and the organic acid salt may be at least one selected from acetates, alkoxides, glutarates, etc., and the like. In addition, the halide may be at least one selected from fluorides, chlorides, bromides, iodides, etc.

[0070] According to an exemplary embodiment, a nickel compound (specifically, a salt or complex) having an oxidation value of 2+ can be used as the nickel precursor. Exemplarily, the nickel compound can be at least one selected from nickel nitrate, nickel sulfate, nickel chloride, nickel carbonate, nickel acetylacetonate complex, nickel acetate, etc., or a hydrate thereof, and specifically, nickel nitrate and / or a hydrate thereof (e.g., Ni(NO3)2·6H2O) can be used.

[0071] According to an exemplary embodiment, the nickel precursor may be provided in the form of a solution, and the solvent may be at least one selected from water, an aliphatic alcohol having 1 to 4 carbon atoms (e.g., methanol, ethanol, propanol (e.g., n-propanol and / or iso-propanol), and / or n-butanol), and specifically, propanol may be used. According to a specific embodiment, a mixed solvent of alcohol and water may be used as the solvent. In this case, the volume ratio of alcohol:water may be adjusted, for example, in the range of about 1.5 to 5:1, preferably about 2 to 4:1, and more preferably about 2.5 to 3.5:1, but this is understood as an exemplary gist.

[0072] In addition, the concentration of the nickel precursor in the nickel precursor solution is not particularly limited, but can be adjusted in the range of, for example, about 0.05 to 0.5 mmol, preferably about 0.08 to 0.3 mmol, and more preferably about 0.1 to 0.2 mmol, taking into consideration the degree of ion adsorption, and this is understood as an illustrative example.

[0073] According to an exemplary embodiment, the iron (Fe)-containing polymer / carbon composite may be added to the nickel precursor solution prepared as described above. Alternatively, a dispersion of the iron (Fe)-containing polymer / carbon composite (e.g., a mixed liquid medium of alcohol and water) may be prepared, and then the nickel precursor or its solution may be added thereto. According to an exemplary embodiment, the weight ratio of the iron (Fe)-containing polymer / carbon composite:nickel precursor may depend on the amount of nickel supported in the final catalyst, and may be adjusted, for example, in the range of 1:about 0.001-0.1, preferably 1:about 0.005-0.06, and more preferably 1:about 0.01-0.03, taking into account the amount of nickel that is not actually supported, but this is understood as an exemplary gist.

[0074] Referring again to FIG. 1, a pyrolysis step may be performed to form a diatomic metal catalyst in which iron and nickel are each supported in monoatomic form from the NiFe-polymer / carbon composite formed by the introduction of the nickel precursor.

[0075] According to an exemplary embodiment, the pyrolysis may be performed under an inert atmosphere, and such an inert atmosphere may be formed by at least one gas selected from, for example, argon, nitrogen, helium, etc., and more specifically, may be performed under a nitrogen atmosphere. In addition, the pyrolysis temperature may be adjusted to, for example, a temperature above about 700° C., preferably within a temperature range of about 720 to 1000° C., more preferably within a temperature range of about 750 to 900° C. In this case, the heating rate in the pyrolysis stage may be adjusted in consideration of the degree of aggregation of metal ions, and may be, for example, within a range of about 0.5 to 8° C. / min, preferably about 1 to 6° C. / min, more preferably about 2 to 4° C. / min.

[0076] In this embodiment, the polymer / carbon composite is converted into a nitrogen-doped carbon (NC) nanostructure by pyrolysis, and at the same time, the metal components, i.e., nickel (Ni) and iron (Fe), can provide catalytic active sites by bonding (coordinating or chelating) with the nitrogen atoms doped in the nitrogen-doped carbon nanostructure acting as a support to form Ni-N4 sites and Fe-N5 sites, respectively.

[0077] At this time, the bond or connection form between the Ni-N4 site and the Fe-N5 site may be affected by the pyrolysis temperature, and therefore, as described below, the pyrolysis temperature may be adjusted so that the nickel (Ni) at the Ni-N4 site and the iron (Fe) at the Fe-N5 site are not directly connected to each other, but are indirectly connected to each other via nitrogen while adjacent to each other. However, the pyrolysis temperature for realizing a desired metal arrangement or connection form may be changed or adjusted depending on the properties of the nitrogen-doped carbon nanostructure to be formed together, the carbon structure, the nitrogen content, the chemical structure of the nitrogen source, etc., rather than being fixed or set to a specific temperature level. At this time, if the pyrolysis temperature is lower than a specific level, nickel (Ni) and iron (Fe) may be directly connected, so the connection form of nickel and iron in the catalyst can be changed by adjusting the pyrolysis temperature.

[0078] On the other hand, the pyrolysis reaction time may affect the coordination number of nickel and iron with nitrogen, the carbon conductivity, the type and content of functional groups, etc., and therefore may be adjusted in consideration of this to, for example, a maximum of about 8 hours, preferably about 0.1 to 3 hours, and more preferably about 0.5 to 2 hours.

[0079] As in the illustrated embodiment, a nitrogen-containing polymer in which iron is introduced into carbon is formed by oxidative polymerization using an iron-based oxidant, and then a nickel precursor is attached and then pyrolyzed to form a nickel (Ni)-iron (Fe) / NC diatomic metal catalyst. This method is advantageous in that the iron precursor acts as an oxidant and is doped at the same time, so no additional oxidant is used.

[0080] According to an exemplary embodiment, after pyrolysis, metals (Ni and / or Fe) that are not bonded to nitrogen atoms and metal particles that have aggregated at high temperatures can be removed, while selectively performing acid washing or acid leaching to distribute nickel and iron in the nitrogen-doped carbon nanostructure in a single atomic form. In this case, the acid used in the acid washing step can be used. However, the concentration of the acid can be adjusted to a lower level, for example, about 0.3 to 2 M, preferably about 0.5 to 1.5 M, and more preferably about 0.8 to 1.2 M, but this is to be understood as an exemplary purpose. Also, pyrolysis or pyrolysis and acid washing can be performed, and a biatomic metal catalyst can be obtained by performing at least one of conventional post-treatments, such as at least water washing and drying. Such post-treatment processes are widely known in the art, and further detailed description will be omitted.

[0081] Meanwhile, in the nickel-iron diatomic metal catalyst according to the present embodiment, the nickel and iron bonded to nitrogen are adjacent to each other in the nitrogen-doped carbon nanostructure and indirectly connected through the nitrogen, which may have a significant effect on the electronic structure between them. As a result, it is believed that low overpotential, high current density, and high carbon monoxide selectivity can be achieved by controlling the adsorption strength with the carbon dioxide conversion intermediate.

[0082] In this regard, the CO2 uptake capacity (25°C) of the single atom catalyst may be, for example, at least about 1.5 μmol / g, preferably about 1-4 μmol / g, and more preferably in the range of about 2-3 μmol / g.

[0083] Carbon dioxide reduction reaction electrode (catalytic electrode) and system According to another embodiment of the present disclosure, a diatomic transition metal catalyst of nickel (Ni) and iron (Fe) can be loaded onto an electrochemical electrode and used to realize a carbon dioxide conversion system (specifically, selectively reducing carbon dioxide to carbon monoxide). In particular, the electrode loaded with the catalyst can be used as a cathode (reducing electrode) where carbon monoxide is generated in the carbon dioxide conversion system.

[0084] According to an exemplary embodiment, during the manufacture of an electrode, the catalyst may be loaded onto a conductive substrate. The loading method is not particularly limited, and methods known in the art, such as loading using a slurry, deposition, spray coating, etc., may be applied.

[0085] As an example, in the slurry loading method, a slurry of the previously produced catalyst (the dispersion medium may be at least one selected from the group consisting of alcohols having 1 to 4 carbon atoms (e.g., methanol, ethanol, propanol, etc.) and water (e.g., distilled water)) can be produced. In this case, the concentration of the catalyst slurry may be adjusted, for example, within a range of about 5 to 30% by weight, preferably about 10 to 20% by weight. Thereafter, the slurry is applied to an electrode substrate (e.g., a conductive substrate) and then dried to produce a catalyst electrode.

[0086] According to another embodiment, a catalyst can be loaded onto a substrate using a deposition method, and at this time, the catalyst layer loaded can be adjusted by adjusting the deposition rate, drying temperature, etc., and cleaning can be performed after deposition.

[0087] According to still another embodiment, spray coating can be applied, which is a method of preparing a coating liquid in the form of a mist and applying it to a substrate. Examples of such methods include an air spray method (using compressed air to prepare a coating liquid in the form of a mist and spraying it onto a substrate), an ultrasonic spray method (using ultrasonic waves to form a coating liquid in the form of droplets and apply it), and an electrostatic spray method (applying a high voltage to charge the coating liquid inside the nozzle, and forming a mist by the repulsive force of the charge and applying it).

[0088] Meanwhile, according to an exemplary embodiment, the substrate on which the carbon dioxide conversion catalyst is loaded may have various shapes such as a plate, a rod, a mesh, a disk, a wire, paper, etc. Also, the conductive substrate may be made of a material that can maintain conductivity even when exposed to an oxidizing atmosphere, and may be made of a material such as at least one selected from valve metals (specifically, titanium, aluminum, chromium, etc.), stainless steel, etc. (including alloys), carbon, etc.

[0089] In an exemplary embodiment, the amount of catalyst loaded is, for example, about 0.2 to 5 mg / cm on an electrode basis. 2 , preferably about 0.5 to 3 mg / cm 2 , more preferably about 0.8 to 2 mg / cm 2 , but this is understood as being for illustrative purposes only.

[0090] According to one embodiment of the present disclosure, a carbon dioxide conversion system can be realized in which carbon dioxide is reduced by using the electrochemical electrode as a cathode to generate carbon monoxide at the cathode and oxygen at the anode. Specifically, when a voltage is applied from an external power source, electrons are supplied to the cathode, which react with carbon dioxide at the cathode to generate carbon monoxide gas and hydroxide ions (OH - ) is generated. At this time, the carbon monoxide gas generated is discharged to the outside, and the hydroxide ions move to the anode. The hydroxide ions that move to the anode may lose electrons (be oxidized) and be converted to oxygen gas, after which they may be discharged.

[0091] In this regard, the carbon dioxide conversion system basically includes a pair of opposing electrodes (i.e., an anode and a cathode), each of which is electrically connected to an external power source (e.g., a potentiostat, a battery, etc.). In addition, the three-electrode system may further include a reference electrode. Such a reference electrode may be selected from the group consisting of Ag / AgCl, a saturated calomel electrode (SCE), Hg / HgO, and Hg / Hg2SO4, and specifically, Ag / AgCl (3M NaCl) may be used.

[0092] According to an exemplary embodiment, the carbon dioxide conversion system uses, as a cathode, an electrochemical electrode containing or having the above-mentioned catalyst attached thereto, as one of a pair of electrodes, and the remaining electrode, the anode, may be of a type known in the art. In this regard, the anode may also be made of a conductive material. As an example, a conductive material applicable to the cathode may be selected from a type that exhibits properties such as easy generation of carbon monoxide and not being decomposed even when in contact with an electrolyte (e.g., an aqueous electrolyte) and that exhibits a particularly low overvoltage, and may be at least one (including an alloy) selected from nickel, carbon, titanium, stainless steel, etc. In the electrochemical carbon dioxide conversion system according to a specific embodiment, each of the cathode and the anode may be operated in a state of being 100% in contact with or immersed in an electrolyte-containing aqueous solution.

[0093] Meanwhile, according to an exemplary embodiment, an electrolyte aqueous solution (which may be alkaline) in which an electrolyte is dissolved in an aqueous medium may be supplied in the carbon dioxide conversion system. In this case, the electrolyte may be at least one selected from potassium hydroxide, potassium hydrogen carbonate, potassium bicarbonate, sodium hydrogen carbonate, sodium hydroxide, lithium hydroxide, and the like, and specifically may be potassium hydrogen carbonate. Exemplarily, the concentration of the electrolyte may be in the range of, for example, about 0.05 to 3 M, preferably about 0.07 to 2 M, and more preferably about 0.1 to 1 M. In addition, the pH of the electrolyte-containing aqueous solution may be adjusted in the neutral or basic region, for example, in the range of about 6.5 to 14, preferably about 7 to 14, and more preferably about 8 to 14.

[0094] Alternatively, the system can be configured using a polymer electrolyte membrane or the like as a separator. Such a separator is typically an ion exchange membrane (e.g., an anion exchange membrane) that is located between the cathode and the anode and separates the anode compartment from the cathode compartment. In this regard, the separator material may be selected from a porous ceramic membrane (e.g., a zirconia-based membrane), a porous polymer membrane (e.g., a polyolefin-based, more specifically, a polypropylene-based membrane), a solid polymer electrolyte membrane (an ion exchange membrane made of a perfluorinated sulfonic acid polymer material such as Nafion), and the like.

[0095] Generally, under thermodynamic standard conditions, the reduction reaction of carbon dioxide occurs near 0 V (vs. RHE), but when considering the concentration range of hydrogen ions that actually participate in the reaction, it occurs at a negative potential, and when considering the reaction rate, a higher overvoltage is required to electrochemically reduce carbon dioxide. In addition, it is preferable for the reduction reaction of carbon dioxide to suppress the hydrogen evolution reaction (HER), which occurs in a similar reduction potential range. The potentials at which currents of the same strength flow in such a pair of opposing electrodes have different values ​​at each electrode, and the voltage at this time corresponds to the overvoltage at each electrode.

[0096] In a carbon dioxide conversion system including an electrochemical electrode using the composite catalyst according to this embodiment, a reduction reaction can be performed at a low overvoltage. For example, when carbon monoxide is produced from the cathode, the system can operate at a low overvoltage. The carbon dioxide reduction reaction may be performed at, for example, about 15 to 40°C, preferably about 20 to 30°C, and more preferably at room temperature.

[0097] When the electrochemical electrode loaded with the single atom catalyst according to the present embodiment is used as a cathode, for example, an aqueous electrolyte solution of 0.1 M KHCO3 (pH 8.3) and a current of 200 mA / cm 2 Under current density conditions, the cell voltage may be, for example, about 3.3 V or less, preferably about 3.2 V or less, more preferably about 3 V or less, and particularly preferably about 2.88 V or less.

[0098] Meanwhile, the Faraday efficiency (FE) is an index for evaluating the efficiency and selectivity of an electrochemical reaction, and may be expressed by the following Equation 1.

[0099]

number

[0100] where z is the number of electrons, n is the molar ratio of products, I is the applied current, t is the reaction duration, and F is the Faraday constant.

[0101] In this regard, under the conditions mentioned above, the faradaic efficiency (FE) may be at least about 90%, preferably at least about 93%, more preferably at least about 95%, and especially preferably at least about 97%.

[0102] Hereinafter, preferred examples will be presented to aid in understanding the present invention. However, the following examples are provided only to facilitate understanding of the present invention, and the present invention is not limited thereto.

[0103] Working Example Details regarding the materials used in this example, the analysis of the catalysts, and the electrochemical performance tests are as follows.

[0104] A. Substance - The Vulcan XC-72R Carbon was purchased from the Fuel cell store. - Pyrrole (C4H5N) monomer, nitric acid, sulfuric acid, potassium bicarbonate, propanol, and nickel nitrate hexahydrate were each purchased from Sigma-Aldrich. - Iron(III) chloride hexahydrate was purchased from Alfa Aesar. - Sigracet 39BB carbon paper and commercial Ag / C electrodes were purchased from Dioxide Materials. - Deionized water (DI, 18 MΩ cm) was purchased from Millipore and used throughout the entire experimental process.

[0105] B. Physicochemical catalyst analysis - High-resolution transmission electron microscopy (HR-TEM) and elemental mapping analysis were performed using a JEM-2100F equipped with a HAADF-STEM detector. - X-ray diffraction (XRD; PANalytical) was used to confirm the metal crystal plane. Measurements were taken at 40 kV and 100 mA using Cu Kα radiation, with a scan speed of 6° per minute at 0.01° intervals, and only the range of 10~80° was measured. - Using X-ray absorption fine structure (XAFS; PLS-II) spectroscopy, Ni K-edge XAFS spectra in the photon energy range of 8132-9078 eV and Fe K-edge XAFS spectra in the photon energy range of 6910-8082 eV were obtained. - The metal content (wt%) in the produced catalyst was determined using inductively coupled plasma atomic emission spectroscopy (ICP-AES, NexION 300X). - XPS spectra of surface elements were obtained using a high-performance X-ray photoelectron spectroscopy (XPS; VG multilab 2000). - Using BET analysis (Brunauer-Emmett-Teller analysis; Quadrasorb SI), the N2 sorption isotherm was obtained at -196°C, and the specific surface area (m 2 / g) was calculated.

[0106] C. Electrochemical experiment Using a spray gun, apply 1 mg / cm2 to carbon paper (Sigracet 39BB, Dioxide Materials). 2 A commercial IrO2 catalyst and a Sustainion® anion exchange membrane (Dioxide Materials) were used as the oxidizing electrode and the separating membrane, respectively. The separating membrane was placed between the oxidizing electrode and the reducing electrode, and the active area was 5 cm2. 2 A membrane electrode assembly (MEA) of a certain size was formed, and finally an electrochemical cell was assembled.

[0107] The electrolyte used was a 0.1 M KHCO3 solution (neutral pH), which was circulated to the oxidizing electrode side at a rate of 3 mL / min, and carbon dioxide gas was continuously supplied to the reducing electrode side at a flow rate of 30 mL / min.

[0108] Electrochemical carbon dioxide conversion performance was measured using chronopotentiometry at 200 mA / cm 2The analysis was performed under the above conditions, and the generated gas was analyzed by gas chromatography (Agilent 7890).

[0109] Example 1 Fabrication of NiFe-DAC Vulcan XC-72R Carbon (Fuel cell store) was treated with 6M HNO3 and 6M H2SO4 for 1 day and then dried. 400mg of dried carbon was dispersed in a mixture of propanol (sigma) / distilled water (volume ratio 3:1), and pyrrole monomer (2.2mmol) dispersed in 10mL of distilled water was added and stirred for 30 minutes to prepare a suspension.

[0110] Then, iron(III) chloride hexahydrate (4.4 mmol) was dissolved in 10 mL of distilled water, added to the above suspension, and stirred for 4 hours to produce an Fe-doped polypyrrole-carbon composite (Fe-PPyC).

[0111] Next, NiFe-DAC was produced using incipient wetness impregnation. Specifically, 150 mg of Fe-PPyC synthesized previously was added to a metal precursor solution in which 0.11 mmol of nickel nitrate hexahydrate was dissolved in 4 mL of propanol / distilled water (volume ratio 3:1), and the solution was sonicated for 2 hours and then dried. Then, the solution was pyrolyzed at 800°C for 1 hour under a N2 atmosphere, and finally, NiFe-DAC (diatomic catalyst) was obtained by removing impurities by washing with a 1M H2SO4 solution.

[0112] Comparative Example 1 Fe-SAC production A catalyst was produced by the same procedure as in Example 1, except that Fe-PPyC was pyrolyzed without using nickel nitrate hexahydrate, to obtain an Fe-SAC (single atomic catalyst).

[0113] Comparative Example 2 Manufacturing of NiFe-DAC (Direct) NiFe-DAC(Direct) was obtained by preparing a catalyst according to the same procedure as in Example 1, except that the pyrolysis temperature under N2 atmosphere was set at 700°C.

[0114] Comparative Example 3 A commercial reducing electrode catalyst, Ag / C (Dioxide Materials), was prepared.

[0115] Catalyst characterization - HADDF-STEM analysis The NiFe-DAC catalyst prepared in Example 1 was subjected to HADDF-STEM analysis, and the results are shown in FIGS. 2A to 2C.

[0116] Referring to the figure, it was confirmed that the catalyst of Example 1 has a diatomic structure in which Ni and Fe are spaced apart by an average of about 0.27 nm, and in particular, it was confirmed that 65% of the single atoms observed exist in pairs.

[0117] -XRD analysis The XRD patterns of the catalyst according to Example 1 (NiFe-DAC) and the catalysts according to Comparative Example 1 (Fe-SAC and NiFe-DAC(Direct)) are shown in FIG.

[0118] Referring to the figure, no peaks associated with other metals were observed other than the carbon peak (002 plane) at around 22° in either catalyst prepared in Example 1 or Comparative Example 1. This result indicates that the metal is uniformly distributed on the carbon support in a single atomic state without the formation of metal crystal particles.

[0119] - XPS analysis The catalyst (NiFe-DAC) according to Example 1 and the catalyst (Fe-SAC) according to Comparative Example 1 were each subjected to XPS analysis, and the results are shown in FIG.

[0120] Referring to the figure, Ni 2p and Fe 2p peaks are observed in the catalyst (NiFe-DAC) according to Example 1, which indicates that the active metals Ni and Fe are simultaneously present on the carbon support.

[0121] On the other hand, only the Fe 2p peak was observed in the catalyst (Fe-SAC) according to Comparative Example 1, which indicates that only Fe exists as an active metal in the catalyst. In addition, in the case of Fe in NiFe DAC, the Fe 2p peak shifted to a higher binding energy, which confirmed that the electronic structure was changed by the additional introduction of Ni.

[0122] - Analysis of metal content in catalysts The catalysts prepared in Example 1 and Comparative Example 1 were subjected to ICP analysis for metals (Ni and / or Fe), and the results are shown in Table 1 below.

[0123] [Table 1]

[0124] Referring to the above table, it can be seen that Ni and Fe are introduced into the catalyst (NiFe-DAC) according to Example 1.

[0125] - EXAFS analysis EXAFS analysis was carried out on each of the catalyst according to Example 1 (NiFe-DAC) and the catalyst according to Comparative Example 1 (Fe-SAC), and the results are shown in FIG. 5A.

[0126] Referring to the figure, it was observed that both NiFe-DAC and Fe-SAC have Fe-N peaks from the Fe K-edge Fourier-transformed (FT) EXAFS spectrum. This indicates that Fe exists in a monoatomic state bound to N. In addition, the Ni FT-EXAFS spectrum shows that Ni in NiFe-DAC exists in a monoatomic state bound to N. As a result of EXAFS fitting, it is determined that Ni is bound to four N atoms and Fe is bound to five N atoms.

[0127] On the other hand, an EXAFS analysis was carried out on the catalyst (NiFe-DAC(Direct)) according to Comparative Example 2, and the result is shown in FIG. 5B.

[0128] Referring to the figure, in the catalyst according to Comparative Example 2 (NiFe-DAC(Direct)), in addition to the Fe-N peak indicating a single atomic state, a minor peak indicating an Fe-Ni bond was observed at around 2.5 Å. The above results indicate that NiFe-DAC(Direct) further has an Fe-Ni bond, which affects the electronic structure, and ultimately suggests that the production efficiency of carbon monoxide by carbon dioxide conversion is different from that of the catalyst according to Example 1.

[0129] - BET analysis The catalyst according to Example 1 (NiFe-DAC) and the catalyst according to Comparative Example 1 (Fe-SAC) were subjected to BET analysis, and the results are shown in FIG. 6. Referring to the figure, the catalysts produced according to Example 1 and Comparative Example 1 have similar pore structures, specific surface areas (approximately 148 to 152 m), and 2 The reason for the similar pore structure is believed to be that they were heat-treated at the same temperature.

[0130] Electrochemical performance evaluation The Faraday efficiency (200 mA / cm) for carbon monoxide production was measured for the catalyst according to Example 1 (NiFe-DAC) and the catalysts according to Comparative Examples 1 to 3 (Fe-SAC, NiFe-DAC (Direct), and Ag / C). 2 The results are shown in FIG.

[0131] As shown in the figure, the NiFe-DAC catalyst showed the highest faradaic efficiency (FE) for carbon monoxide (CO) production at the lowest voltage compared to the single-atom catalysts Fe-SAC, NiFe-DAC (Direct), and commercial Ag / C.

[0132] Considering the above-mentioned physicochemical analysis results, it is believed that in the NiFe-DAC catalyst, the Ni-N4 site and the Fe-N5 site are adjacent to each other, inducing a synergistic effect due to strong electrical interaction, thereby appropriately controlling the electronic structure of the NiFe-DAC catalyst, thereby accelerating the conversion reaction of carbon dioxide to carbon monoxide.

[0133] Simple modifications or variations of the present invention may be readily utilized by a person of ordinary skill in the art, and any such modifications or variations may be deemed to fall within the scope of the present invention.

Claims

1. (i) a support comprising nitrogen-doped carbon nanostructures ((N-C) nanostructures); and (ii) nickel (Ni) and iron (Fe), each deposited in monoatomic form on said support; Including, Nickel (Ni) is linked to each of the four surrounding nitrogen atoms, while iron (Fe) is linked to each of the five surrounding nitrogen atoms, Ni-N 4 Site and Fe-N 5 Create a site; and Ni-N 4 Ni and Fe-N sites 5 An electrochemical catalyst in which the Fe atoms at the sites are adjacent to each other and indirectly connected via nitrogen.

2. 2. The catalyst according to claim 1, wherein the nickel (Ni) content is in the range of 0.1 to 10 wt % and the iron (Fe) content is in the range of 0.1 to 10 wt %.

3. The catalyst according to claim 2, wherein the atomic ratio of nickel (Ni) to iron (Fe) in the catalyst is 1:0.4-1.

6.

4. The catalyst is 100 to 300 m 2 / g specific surface area (BET) and 0.1-0.5 cm 3 Catalyst according to claim 1, characterized in that it exhibits a pore volume of 100 / g.

5. The catalyst according to claim 1, wherein the nitrogen content in the nitrogen-doped carbon nanostructure is in the range of 1 to 12 atomic %.

6. a) forming an iron (Fe)-containing polymer / carbon composite by attaching a nitrogen-containing monomer to carbon and polymerizing in-situ using an iron-based oxidizing agent; b) depositing a nickel precursor onto the iron (Fe)-containing polymer / carbon composite to form a NiFe-polymer / carbon composite; c) pyrolyzing the NiFe-polymer / carbon composite to deposit nickel (Ni) and iron (Fe) in monoatomic form on a support comprising nitrogen-doped carbon nanostructures ((N-C) nanostructures); Including, Nickel (Ni) is linked to each of the four surrounding nitrogen atoms, while iron (Fe) is linked to each of the five surrounding nitrogen atoms, Ni-N 4 Site and Fe-N 5 Create a site; and Ni-N 4 Ni and Fe-N sites 5 A method for producing an electrochemical catalyst, wherein the Fe atoms at the sites are adjacent to each other and indirectly connected via nitrogen.

7. 7. The method of claim 6, wherein the carbon comprises at least one selected from the group consisting of carbon black, graphene, carbon nanotubes (CNTs), and fullerenes.

8. 7. The method of claim 6, wherein the carbon has nanoscale dimensions and an average particle size of 10-200 nm.

9. The carbon has a viscosity of at least 1.5 Scm -1 The method for producing an electrochemical catalyst according to claim 6, characterized in that the catalyst exhibits a conductivity of 0.1 to 1.

0.

10. The method for producing an electrochemical catalyst according to claim 6, wherein the nitrogen-containing monomer is at least one selected from the group consisting of urea, melamine, ammonia, adenine, pyrrole, acrylonitrile, phenanthroline, pyrazole, vinylpyridine, pyrimidine, piperazine, pyran, carbamide, morpholine, imidazole, 1-methylimidazole, 2-methylimidazole, quinoxaline, aniline, benzimidazole, ethylenediamine, and cyanamide.

11. The method for producing an electrochemical catalyst according to claim 6, wherein the iron-based oxidant is an Fe(II) oxidant and / or an Fe(III) oxidant.

12. The Fe(II) oxidant is Fe(NO 3 ) 2 , FeSO 4 , Fe(acac) 2 , Fe(tfac) 2 , Fe(OAc) 2 , FeCl 2 , FeBr 2 and FeI 2 and hydrates thereof; and The Fe(III) oxidant is Fe(NO 3 ) 3 , Fe 2 (SO 4 ) 3 , Fe(acac) 3 , Fe(tfac) 3 , Fe(OAc) 3 , Fe(OTs) 3 , Fe(OTf) 3 , FeCl 3 , FeBr 3 and FeI 3 12. The method for producing an electrochemical catalyst according to claim 11, wherein the catalyst is at least one selected from the group consisting of:

13. 7. The method for producing an electrochemical catalyst according to claim 6, wherein the nickel precursor is at least one selected from the group consisting of nickel nitrate, nickel sulfate, nickel chloride, nickel carbonate, nickel acetylacetonate complex, nickel acetate, and hydrates thereof.

14. 7. The method of claim 6, wherein the pyrolysis of step c) is carried out at a temperature above 700° C. for up to 8 hours.

15. Electrode substrate; and a diatomic metal catalyst loaded on said electrode substrate; An electrode for a carbon dioxide reduction reaction comprising: The diatomic metal catalyst is (i) a support comprising nitrogen-doped carbon nanostructures ((N-C) nanostructures); and (ii) nickel (Ni) and iron (Fe), each deposited in monoatomic form on said support; an electrochemical catalyst comprising: In the diatomic metal catalyst, nickel (Ni) is bonded to each of the four surrounding nitrogen atoms, while iron (Fe) is bonded to each of the five surrounding nitrogen atoms, forming Ni-N 4 Site and Fe-N 5 Create a site; and Ni-N 4 Ni and Fe-N sites 5 The Fe at the sites are adjacent to each other and indirectly connected via nitrogen, the electrode.

16. The loading of the diatomic metal catalyst in the electrode is 0.2 to 5 mg / cm 2 16. The electrode according to claim 15, characterized in that

17. An anode and a cathode as electrochemical electrodes electrically connected to an external power source; and an aqueous electrolyte disposed between the anode and the cathode; A carbon dioxide reduction system comprising: When a voltage is applied from the external power source, oxygen is generated from the anode side, and carbon monoxide is generated from the cathode side. the cathode comprises a diatomic metal catalyst loaded on an electrode substrate; The diatomic metal catalyst is (i) a support comprising nitrogen-doped carbon nanostructures ((N-C) nanostructures); and (ii) nickel (Ni) and iron (Fe), each deposited in monoatomic form on said support; an electrochemical catalyst comprising: In the diatomic metal catalyst, nickel (Ni) is bonded to each of the four surrounding nitrogen atoms, while iron (Fe) is bonded to each of the five surrounding nitrogen atoms, forming Ni-N 4 Site and Fe-N 5 Create a site; and Ni-N 4 Ni and Fe-N sites 5 The Fe at the sites are indirectly connected to each other while being adjacent to each other via nitrogen.

18. The electrolyte comprises at least one selected from the group consisting of potassium hydroxide, potassium hydrogen carbonate, potassium bicarbonate, sodium hydrogen carbonate, sodium hydroxide, and lithium hydroxide; and 18. The system of claim 17, wherein the pH of the aqueous electrolyte is controlled within the range of 6.5 to 14.

Citation Information

Patent Citations

  • Oxygen reduction catalyst, method for producing the catalyst, electrode, method for producing the electrode, fuel cell, air cell and electronic device

    JP2010221157A

  • Cathode electrode for gas diffusion electrolytic flow cell, and gas diffusion electrolytic flow cell

    JP2023017501A

  • Catalyst for organic carbonate synthesis and method for producing same, electrode for organic carbonate synthesis, cell for organic carbonate synthesis, method for producing organic carbonate, and synthesis system

    WO2022025138A1